2015
DOI: 10.1097/psy.0000000000000159
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Life Events and Allele-Specific Methylation of the Serotonin Transporter Gene (SLC6A4) in Adolescents

Abstract: Our findings demonstrate a higher level of SLC6A4 methylation after SLEs in adolescents, with a more pronounced association for SLEs during adolescence than during childhood. Considering the allele-specific sensitivity of SLC6A4 methylation to SLEs, this study may help clarify the role of SLC6A4 in the development of affective disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 48 publications
(67 reference statements)
1
24
0
1
Order By: Relevance
“…Swartz et al found that of all the environmental variables tested, only lower SES at the first wave of the study predicted greater increases in SLC6A4 DNA methylation at wave 2. Other recent work has identified childhood maltreatment and SLEs to be associated with differential 5mC in this gene; however, it should be noted that these earlier studies focused largely on physical and sexual abuse, rather than emotional neglect, as tested in this study, and that objective ratings of SLEs were used as the predictor of interest, rather than subjective ratings as is frequently used in related work. Swartz et al's findings are in line with emerging work that has begun to demonstrate associations between low SES and higher 5mC in the SLC6A4 promoter region , although these previous findings have often been specific to subgroups within larger samples.…”
Section: Low Ses Uniquely Predicts Greater Slc6a4 Methylation Change supporting
confidence: 59%
See 1 more Smart Citation
“…Swartz et al found that of all the environmental variables tested, only lower SES at the first wave of the study predicted greater increases in SLC6A4 DNA methylation at wave 2. Other recent work has identified childhood maltreatment and SLEs to be associated with differential 5mC in this gene; however, it should be noted that these earlier studies focused largely on physical and sexual abuse, rather than emotional neglect, as tested in this study, and that objective ratings of SLEs were used as the predictor of interest, rather than subjective ratings as is frequently used in related work. Swartz et al's findings are in line with emerging work that has begun to demonstrate associations between low SES and higher 5mC in the SLC6A4 promoter region , although these previous findings have often been specific to subgroups within larger samples.…”
Section: Low Ses Uniquely Predicts Greater Slc6a4 Methylation Change supporting
confidence: 59%
“…Honing in on a particular gene that has previously been associated with differential stress reactivity and early life adversity – the serotonin transporter promoter ( SLC6A4 ) – they tested whether exposure to a number of environmental risk factors was associated with differential changes in 5mC in the promoter region, a gene region that serves to modulate gene function, including within this locus . Environmental risk factors of interest included emotional neglect during childhood, stressful life events (SLEs) during the prior year, and low SES, all of which had shown associations with differential SLC6A4 5mC in previous cross‐sectional studies . They further tested whether the extent of 5mC change was associated with a brain‐level indicator of differential risk of depression, specifically changes in threat‐related amygdala reactivity, which had been previously associated with depression risk in cross‐sectional studies and with age‐related changes in reactivity in the absence of depression in the authors’ prior work .…”
Section: Can Elevated Premorbid Risk Of Depression Be Indexed By Epigmentioning
confidence: 99%
“…All that granted, Van der Knaap et al (2014) demonstrate a higher level of serotonin transporter gene methylation after stressful life events in adolescents, with a more pronounced association for stressful events during adolescence than during childhood.…”
Section: Biological Consequences Of Parental Loss and Other Childhoodmentioning
confidence: 90%
“…Based on previous research 6, 13 , we hypothesized that increased methylation related to early pain exposure would result in altered emotional regulation profile in preterm children compared to full-term counterparts. As DNA methylation is susceptible to additional environmental exposures later in life, 18,19 we controlled for cumulative exposure to adversities that might have occurred from birth to 4.5 years of age.…”
Section: Introductionmentioning
confidence: 99%